The relationship between coach and player training load perceptions in professional soccer - Eduardo Redkva, P.; Gregorio da Silva, S.; Ricetti Paes, M.; dos Santos, J. W. (Perceptual and Motor Skills, 2017)
The training load imposed and perceived by coaches and soccer players, respectively, was compared for three weeks of the basic preparatory period of a professional soccer team through session ratings of perceived exertion (S-RPE). Participants were 24 professional Brazilian soccer players (all males, age: 24.1 ± 3.4 years) and their coaches. Athletes responded to the scale of perceived exertion (scores from 0 to10) after the training, while the coaches completed the scale prior to the training session, based on prior planning. The t-test for independent samples was used to compare SRPE responses, and the Pearson correlation test was used to examine possible correlations between the parameters analyzed. There were no statistical differences between perceptions of prescribed (coaches) and experienced (players) S-RPE, and moderate correlations were found between these parameters (r = .60; p = .003). No statistically significant group differences were found in the perceived exertion during any of three types of training: physical, technical, or tactical. The results suggest that the S-RPE prescribed during the preseason period (by coaches) was not different from that perceived by professional soccer players. ABSTRACT FROM AUTHOR